Effect of the model’s geometry in fretting fatigue life prediction - J. Vázquez; C. Navarro; J. Domínguez (Fracture and Structural Integrity)
This paper analyses the influence that the type of geometry used to obtain the stress/strain fields in a cylindrical contact has on fretting fatigue life predictions. In addition, this work considers the effect that the fatigue crack shape assumed has on these fretting fatigue life predictions. The strain/stress fields are calculated using a series of finite elements models that consider the following three types of behaviour: plane stress, plane strain (2D geometries) and 3D. Each of these models gives a different crack initiation life and a different evolution of the stress intensity factor (SIF), which are calculated using the weight function method. These models therefore provide different fretting fatigue life predictions. Finally, the lives obtained using the numerical models are compared with experimental lives.